Iron in Neurodegeneration – Cause or Consequence? - Ndayisaba, Alain; Kaindlstorfer, Christine; Wenning, Gregor K. (Frontiers in Neuroscience, 2019)
Iron dyshomeostasis can cause neuronal damage to iron-sensitive brain regions. Neurodegeneration with brain iron accumulation reflects a group of disorders caused by iron overlad in the basal ganglia. High iron levels and iron related pathogenic triggers have also been implicated in sporadic neurodegenerative diseases including Friedreich´s ataxia, Alzheimer’s disease (AD), Parkinson’s disease (PD) and multiple system atrophy (MSA). Iron induced dyshomeostasis within vulnerable brain regions is still insufficiently understood. This review summarizes major pathophysiological mechanisms of neurodegeneration and establishes a connection to iron dyshomeostasis aiming to determine the role of iron in disease pathogenesis.